ANALISIS KEMANDIRIAN FISKAL, KETERGANTUNGAN FISKAL, DAN EFEKTIVITAS FISKAL PROVINSI KALIMANTAN UTARA PERIODE 2017-2022 - Kumba Digdowiseiso; Fitri Andriani; Nicolaus Petrus L. W (Jurnal Ilmiah Global Education, 2023)
This research study aims to analyze the aspects of Fiscal Independence, Fiscal Dependence, and Fiscal Effectiveness of the North Kalimantan Province for the 2017-2022 period. This research is quantitative descriptive research. The average is obtained in the fiscal independence section with a value of ≤0.28, categorized as starting toward regional budgetary independence. Then the fiscal dependence portion of the percentage value obtained is 74,60% which is classified as a very high level of regional fiscal dependence. Furthermore, the fiscal effectiveness portion of the figure obtained is 101,23%, which means it is very effective in implementing the regional Fiscal. Overall, the review of fiscal independence, dependability, and effectiveness proves that there are fluctuating changes every year. Then justifies the influence of the First-Generation Theory in the review studied that the central government's intervention in the regional government of North Kalimantan Province still has an effect in various aspects intended in this study in the form of independence, dependence, and its fiscal effectiveness with the period of the year under study.